Unstable Particles, Gauge Invariance and the Δ++ Resonance Parameters - López Castro, Gabriel (2003)
The elastic and radiative π+p scattering are studied in the framework of an effective Lagrangian model for the Δ++ resonance and its interactions. The finite width effects of this spin-3/2 resonance are introduced in the scattering amplitudes through a complex mass scheme to respect electromagnetic gauge invariance. The resonant pole (Δ++) and background contributions (ρ0, σ, Δ, and neutron states) are separated according to the principles of the analytic S-matrix theory. The mass and width parameters of the Δ++ obtained from a fit to experimental data on the total cross section are in agreement with the results of a model-independent analysis based on the analytic S-matrix approach. The magnetic dipole moment determined from the radiative p+p scattering is mD++=(6.14 ± 0.51) nuclear magnetons